Peace and Reason of State in the Confucius Sinarum philosophus (1687). Issue 159 (1st July 2019) - Canaris, Daniel
Abstract : A persistent feature in Jesuit reports about the late Ming and early Qing was the notion that an enduring peace and concord pervaded the Chinese political system. Although the Jesuits did not invent this association, which was rooted in Greco-Roman historiography, the Jesuit encyclopaedist Antonio Possevino (1533–1611) was the first to link the 'perpetual peace' (perpetua pax) and 'supreme concord' (summa concordia) of the Chinese state to the Confucian intellectual tradition. As the Jesuits' missionary strategy developed under the tutelage of Matteo Ricci (1552–1610), 'public peace' (pax publica) and 'the calm of the Republic' (Republica quies) came to be perceived as the ultimate purpose of the Confucian precepts and one of the hinges on which the aims of Christianity, Confucianism and natural law can be reconciled. The supreme expression of the link between Confucianism and peace can be found in the Confucius Sinarum philosophus (1687), which presented for the first time an accessible translation of three of the four Confucian classics. Yet while retaining the view that pre-Qin Confucianism espoused peace as a central political aim, the Confucius Sinarum philosophus challenged the view that contemporary China could be regarded as a utopic actualization of Confucian peace. This paper will discuss this shift as an attempt to coopt the Chinese political experience as an argument against the pragmatic political philosophy known as 'reason of state', which was perceived by Jesuit thinkers as atheistic and immoral.